Difficulties encountered in the implementation of patient safety protocols in Brazil (Research, Society and Development, 2023)
Introduction: In 2013, Brazil instituted the National Patient Safety Program (PNSP) to promote and implement a safety culture. Thus, health services became obliged to develop and implement such a program. Objective: To analyze the difficulties encountered by the health team in implementing patient safety protocols in Brazilian health units. Methods: This is an integrative review conducted in the Latin American and Caribbean databases in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), Virtual Health Library (BVS), and Google Scholar through the descriptors, patient safety, patient safety protocols, nursing, and implantation published from 2012 to 2022. Result: The initial search found 43 articles, of which 5 were considered relevant, and 38 were excluded because they were duplicates and/or did not present outcomes of interest due to incomplete data or lack thereof. Conclusion: It is concluded that the health teams found several conditions that hinder the implementation of safety protocols, requiring the participation of senior management in the process and the teams' understanding of these procedures' importance.